Learner identity and classroom dynamics: A critical study in ESL contexts - Vendhan, P. Shakthi; Venkatalakshmi, T. Shrimathy (Research Journal in Advanced Humanities, 2025)
The interplay between learner identity and classroom dynamics plays a pivotal role in shaping the outcomes of English as a Second Language (ESL) education. The study investigates how socio-economic factors influence language learning outcomes, the impact of classroom dynamics on student engagement and language acquisition, and the effectiveness of pedagogical strategies that promote inclusive education. A mixed-methods approach was utilized to analyze data from diverse educational settings, including urban and regional schools. The findings reveal a significant correlation between learner identity and ESL performance, with socio-economic background playing a crucial role. Classroom dynamics, including peer interactions and teacher awareness, were found to substantially affect student engagement and language acquisition. Furthermore, the implementation of inclusive pedagogical strategies was shown to enhance learner identity and overall language proficiency. These insights contribute to a deeper understanding of the factors that shape ESL learning environments and offer practical recommendations for educators and policymakers to foster a more inclusive and effective language learning experience